2016
DOI: 10.1016/j.envpol.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

A slight recovery of soils from Acid Rain over the last three decades is not reflected in the macro nutrition of beech (Fagus sylvatica) at 97 forest stands of the Vienna Woods

Abstract: Rigorous studies of recovery from soil acidification are rare. Hence, we resampled 97 old-growth beech stands in the Vienna Woods. This study exploits an extensive data set of soil (infiltration zone of stemflow and between trees area at different soil depths) and foliar chemistry from three decades ago. It was hypothesized that declining acidic deposition is reflected in soil and foliar chemistry. Top soil pH within the stemflow area increased significantly by 0.6 units in both H2O and KCl extracts from 1984 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…In addition, in the ICP Forests network, most plots have normal foliar Bc levels. Berger, Türtscher, Berger, and Lindebner () similarly found adequate Bc nutrition in beech stands in Austria and declining foliar Bc trends despite increasing soil exchangeable cations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, in the ICP Forests network, most plots have normal foliar Bc levels. Berger, Türtscher, Berger, and Lindebner () similarly found adequate Bc nutrition in beech stands in Austria and declining foliar Bc trends despite increasing soil exchangeable cations.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, in the ICP Forests network, most plots have normal foliar Bc levels. Berger, T€ urtscher, Berger, and Lindebner (2016)…”
Section: Decreasing Bc In Soil Solutionmentioning
confidence: 99%
“…Declines in acidic deposition across Europe and North America (Lehmann et al, 2005; Greaver et al, 2012) have led to signs of chemical recovery of soils from acidification (Lawrence et al, 2015; Berger et al, 2016). Lawrence et al (2012) also reported significant Al decreases in the Oa horizon at two sites on the WMNF where red spruce was a major species in the canopy, and a significant Ca decrease in upper B horizon at one of the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing base saturation and pH and decreasing Al ex in organic (Oa) horizon soils have been measured in the northeastern United States (Lawrence et al, 2015). Soil water in Sweden has shown indications of a slow recovery with decreasing inorganic Al and increasing ANC (Pihl Karlsson et al, 2011; Akselsson et al, 2013), and in Austrian beech forests, pH, Ca ex , and Mg ex increased in uppermost soil layers (Berger et al, 2016). …”
mentioning
confidence: 99%